Modern (Financial and Innovative) Formation Determinants of Enterprise Logistics Management Under the Influence of Global Challenges - Komelina, Olha; Komelina, Anna; Galinska, Tatyana; Ashyru Ismayli, Kashasira (International Journal of Engineering and Technology, 2018)
A methodological approach is developed in the construction of enterprise logistics management and its business processes. It is substantiated that under current conditions the effectiveness of the formation of the enterprise's logistics system of determines the influence of innovative and financial determinants. The expediency of taking into account the influence of the risks group on the development of the enterprise and its logistical system, which arise in conditions of increasing global challenges and accompanied by changes in the national environment, is substantiated. The content of innovative financial management that takes into account the peculiarities of the logistics system of the enterprise, provides for the optimal way of financial flows, is based on the concept of the value chain, allows to model the chain of activity of the enterprise and manage it for the purpose of supplying a product or service to the market.Â Â